PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN J&T EXPRESS TANJUNG BARAT (RANCHO) - Ilham Ardiansyah; Muhammad As`ad; Eman Sulaeman (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The goods delivery service business in Indonesia is thriving, especially during the Covid-19pandemic, when people's online shopping activities increase. This makes delivery service providerscompete in making accurate strategies regarding price and service quality in order to meetcustomer needs and create customer loyalty.This study aims to determine how price affectscustomer loyalty, how service quality affects customer loyalty, and how price and service qualitysimultaneously affect customer loyalty at J&T Express in Tanjung Barat (Rancho), SouthJakarta.The research method used was descriptive quantitative method. The sample consisted of 80respondents who were selected using a non- probability sampling technique with the accidentalsampling method. The data was processed by multiple linear regression analysis.The resultsshowed that partially price had a positif and signifikan effect on customer loyalty, which wasindicated by tcount 3.727 > ttable 1.991 with a significance value of 0.000 < 0.05 and an R2 value of0.542. This means that price affects customer loyalty by 54.2%. Service quality partially had apositif and signifikan effect on customer loyalty, which was indicated by tcount 5.857 > ttable 1.991with a significance value of 0.000 <0.05 and an R2 value of 0.626. This means that price affectscustomer loyalty by 62.6%. Simultaneously, price and service quality have a positif and signifikaninfluence on customer loyalty, which is indicated by Fcount 82,931 > Ftable 3.12 with a significancevalue of 0.000 < 0.05 and an R2 value of 0.683 This means that simultaneously price and servicequality affect customer loyalty by 68.3%, with the remaining 31.7% influenced by other variabelsnot examined in this study